Shifting Paradigm: From General Anesthesia to Local Anesthesia in Posterior Segment Surgeries: Doi: 10.36351/pjo.v36i3.1001 - Riaz, Sidrah; Khan, Muhammad Tariq; Ahmad, Munir; Butt, Nadeem Hafeez; Chaudhary, Shabana (Pakistan Journal of Ophthalmology, 2020)
Purpose: To evaluate the methods of anesthesia in posterior segment surgeries. Study Design: Cross sectional survey. Place and Duration of Study: Akhtar Saeed Medical College, from April 2017 to May 2019. Material and Methods: Two hundred and three patients who underwent posterior segment surgeries were selected. Average surgery time was 45 minutes under local anesthesia (LA). All patients whose surgery was performed in general anesthesia (GA), had at least 6 hours hospital stay and four hours nothing by mouth before and after procedure. Patient age, gender, indication for surgery, type of surgery performed and type of anesthesia were noted. Data was analyzed by using SPSS 25. Results: Total 203 patients were included in study, 122 (60.1%) male and 81 (39.9%) females. General anesthesia (GA) was used in 18.2% surgeries and local anesthesia (LA) was opted in 81.8%. Mean age of patients who underwent GA was 30.62 years and 51.71 years for LA. Three major indications for LA were retinal attachment surgery 64 (38.6%), vitreous hemorrhage 20 (12%) and endophthalmitis in 12 (7.2%) patients. Indications for surgery under GA were surgery for retinal detachment in 23 (62.2%), endophthalmitis 6 (16.2%) and removal of silicon oil 2 (5.4%). PPV was done in 64.5% patients under LA and 9.8% in GA but all combined procedures (PPV and scleral buckling) were done under GA. Conclusion: The local anesthesia is favorable for posterior segment ocular surgeries in term of less hospital stay, no need of NPO, fast recovery and cost effectiveness